Deferasirox Efficacy and Safety in Pediatric Beta Thalassemia Major: A Focus on Liver and Renal Function - Hadi , Ameer Muhsin; Naji , Aiub Bassim; Muhssin , Akram Hamdi; Alkhateeb , Dheyaa Aldeen (Journal of Science in Medicine and Life, 2025)
Background: Thalassemia, inherited autosomal recessive disorders, result in reduced or absent globin chain synthesis, causing abnormal hemoglobin and anemia. Chelation therapy and transfusions improve patient lifespan. Objectives: This study evaluated the 3-year efficacy of deferasirox (Exjade) in transfusion-dependent β-thalassemia and assessed changes in liver enzymes, renal function, and serum calcium. Patients and Methods: A retrospective comparative study of 50 β-thalassemia major patients (5-17 years) with baseline serum ferritin >1000 ng/ml was conducted. Baseline and follow-up (8-12 weeks) serum ferritin, S.GPT, S.GOT, creatinine, BUN, and calcium levels were analyzed. Results: Significant serum ferritin reduction was observed, from 3737.88 ng/ml at baseline to 2301.78 ng/ml at 36 months (p<0.05). The mean Exjade dose decreased from 36.41 to 33.03 mg/kg/day (p<0.05). S.GPT and S.GOT increased slightly in the third year, within acceptable limits, while bilirubin decreased (p<0.05). Creatinine showed non-significant fluctuations, but BUN changed significantly (p<0.05). Serum calcium showed a mild initial increase, then decreased (p<0.05). Conclusions: Deferasirox significantly reduces serum ferritin in β-thalassemia major patients at doses ≥30 mg/kg. It has milder liver enzyme effects than deferoxamine, though slight increases occur. Renal hemodynamic effects were mild and reversible over 3 years, with no progressive decline.